Early infant feeding practices in Ireland; current and secular analyses of infant feeding in two prospective birth cohort studies. (2020) - Hemmingway, Andrea; Fisher, Dawn; Berkery, Teresa; Kiely, Mairead E
Abstract: Recognised as the optimum infant feeding method, breastfeeding affords substantial health benefits to mother and infant. Exclusive breastfeeding is recommended to 6 months, with continuation thereafter. In Ireland, data indicates that 60% breastfeed to any extent at hospital discharge and 40% do so at 3 months. However, nationally collected data is limited in detail, particularly with regard to breastfeeding continuation. The ongoing Cork-based COMBINE birth cohort study recruited 456 participants between 2015 and 2017. Through interviewer-led questionnaires, research midwives collected feeding data at hospital discharge, 1, 2, 4, 6 and 9 months of age. Infant feeding was classed as breast (breastmilk as main milk source), combination (both breastmilk and infant formula daily) or infant formula only feeding. Adherence to the World Health Organisation (WHO) recommendation to exclusively breastfeed (breastmilk only, no infant formula, supplementary fluids or solid foods) was examined longitudinally. To explore secular changes, breastfeeding rates in COMBINE were compared to the BASELINE birth cohort study, which recruited participants ( n = 2116) between 2008 and 2011 in the same setting. In COMBINE, 75% of mothers provided any breastmilk (breast or combination) at hospital discharge, of whom 44% breastfed only. Two-fifths (40%), one-third (33%) and one-quarter (24%) breastfed at 1, 4 and 6 months, respectively. Combination feeding of breastmilk and infant formula was prevalent at discharge (31%) and 1 month (20%). Advice from healthcare professionals (31%) and concern baby was hungry (30%) were commonly reported reasons for this practice and throughout the study, mothers who combination fed were more likely to stop breastfeeding altogether than those who breastfed (all P < 0.001). Infant formula only feeding increased from 25% at discharge to 40% at 1 month, 49% at 2 months and 74% at 9 months. Half (45%) of mothers who breastfed did so for less than 4 months and insufficient milk/growth faltering was the most commonly cited reason for cessation (27%). The rate of WHO-defined exclusive breastfeeding was 40% from birth to discharge, 22% to 1 month, 15% to 4 months and 2% to 6 months. The breastfeeding (breastmilk as main milk source) rate at discharge did not differ between our two birth cohorts (44 vs. 40%, P = 0.23), but was significantly higher in COMBINE compared to BASELINE at 2 (36 vs. 27%) and 6 (24 vs. 12%) months (both P < 0.05). While these data provide evidence of some progress towards longer breastfeeding durations, there remains much scope to improve infant feeding practices in Ireland.